2023
DOI: 10.1186/s12891-022-06070-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diaphyseal and metaphyseal ulnar shortening osteotomies for the treatment of ulnar impaction syndrome

Abstract: Background Ulnar shortening osteotomy (USO) is a common surgical procedure for the treatment of ulnar impaction syndrome (UIS). The purpose of this study was to compare the results of metaphyseal and diaphyseal USO.  Methods This retrospective study compared the clinical outcomes and complications of 32 patients who underwent diaphyseal step-cut USO (n = 10), diaphyseal oblique USO (n = 12), or metaphyseal USO (n = 10). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Bone healing is optimized by increasing the apposition of the fusion interface. To obtain the largest surface area for fusion, the level of the metaphyseal bone should be optimized to supply sufficient blood and complete the union [20]. Furthermore, arthrodesis with accurate alignment is important.…”
Section: Discussionmentioning
confidence: 99%
“…Bone healing is optimized by increasing the apposition of the fusion interface. To obtain the largest surface area for fusion, the level of the metaphyseal bone should be optimized to supply sufficient blood and complete the union [20]. Furthermore, arthrodesis with accurate alignment is important.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yang et al . 3 have compared metaphyseal osteotomies with diaphyseal osteotomies and showed that metaphyseal osteotomies have the advantage of shortening operative time and promoting early postoperative pain relief as well as bone healing. However, there is no high level of evidence to support a specific type of osteotomy.…”
mentioning
confidence: 99%